Race in the age of Obama. Part 2 - Cunnigen, Donald; Bruce, Marino A. (Research in race and ethnic relations ;, 2015)
This volume is the second part of a two volume examination of the sociological and cultural impact derivative of Barack Hussein Obama's initial election and re-election as President of the United States. For some scholars and political pundits, the election of the first African-American president was thought to be the start of a post-racial era in the United States. His election/re-election has created a new racial dynamic within the nation. The Obama administration has faced unprecedented political challenges that have led to the deepening of racial divisions and a crystallization of multiple inequities within the country. The editors envision a volume highlighting a number of sociological themes within the following five primary foci: 1) an examination of the 2012 election; 2) the intersection of racial politics with new conservative and voting rights issues; 3) the intersection of race and class with sociocultural issues; 4) an examination of the international perspective of the Obama administration in relationship to the African Diaspora; and 5) an exploration of the potential for multiracial coalitions and social movements to bring about positive structural change.